2007
DOI: 10.1080/17453670610013448
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative gait analysis has a substantial effect on orthopedic decision making in children with cerebral palsy: Comparison between clinical evaluation and gait analysis in 60 patients

Abstract: Background There is still some debate regarding the role of 3-dimensional gait analysis in routine preoperative evaluation of children with cerebral palsy. The aim of this prospective study was to evaluate to what extent introduction of 3-D gait analysis changes preoperative surgical planning.Method Before gait analysis, 60 ambulatory children aged 10 (4-18) years with spastic cerebral palsy had a specific surgical plan outlined, based on clinical examination by orthopedic surgeons. After gait analysis, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 12 publications
1
63
2
Order By: Relevance
“…5 It has been clearly documented that CGA alters surgical decision making and changes the treatment that patients receive. [6][7][8][9][10] However, the implications of these changes in terms of cost and the amount of surgery performed have not been documented. Therefore, the purpose of this large retrospective study was to determine the effects of CGA on the costs of care in ambulatory children with cerebral palsy (CP) and the amount of surgery that these children undergo.…”
mentioning
confidence: 99%
“…5 It has been clearly documented that CGA alters surgical decision making and changes the treatment that patients receive. [6][7][8][9][10] However, the implications of these changes in terms of cost and the amount of surgery performed have not been documented. Therefore, the purpose of this large retrospective study was to determine the effects of CGA on the costs of care in ambulatory children with cerebral palsy (CP) and the amount of surgery that these children undergo.…”
mentioning
confidence: 99%
“…Motion analysis systems and supporting software enable the collection of accurate, repeatable and objective data on the complex dynamic movements patients perform. This type of analysis has shown a demonstrable positive effect on clinical decision-making in the context of gait analysis [5,6]. The ability to provide this data in other rehabilitation settings could enable clinicians to make more informed decisions.…”
Section: Potential Benefits Of Biomechanical Analysis For Rehabilitationmentioning
confidence: 99%
“…A recent systematic review [7] identified numerous retrospective [8][9][10][11][12][13] and prospective studies [14][15][16][17][18][19] demonstrating improvements in gait, gross motor function and quality of life following orthopaedic intervention. 3D gait analysis is commonly used to inform surgical decision making [20][21][22]. A number of indices have been proposed in the literature to measure gait abnormality, including the Gillette Gait Index (GGI) [23], Gait Deviation Index (GDI) [24] and Gait Profile Score (GPS) [25].…”
Section: Introductionmentioning
confidence: 99%